2019
DOI: 10.1128/msphere.00387-19
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Adaptation to Species-Specific Gut Microbiota in House Mice

Abstract: The gut microbial communities of mammals have codiversified with host species, and changes in the gut microbiota can have profound effects on host fitness. Therefore, the gut microbiota may drive adaptation in mammalian species, but this possibility is underexplored. Here, we show that the gut microbiota has codiversified with mice in the genus Mus over the past ∼6 million years, and we present experimental evidence that the gut microbiota has driven adaptive evolution of the house mouse, Mus musculus domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
(39 reference statements)
2
35
0
Order By: Relevance
“…This was particularly evident for some bacterial taxa such as Actinobacteria (sp.1 and sp.2), Geobacillus and Wolbachia, which were hosted by P. horvathi and P. tridentatus ( Figure 5). The results are consistent with recent studies showing strong associations between host phylogenetic divergence and phylogenetic divergence of the associated microbiome in several taxa, including humans [72,73], mice [74], birds [75], lizards [76] and insects [77].…”
Section: Codiversification Between Water Striders and Their Microbiomesupporting
confidence: 92%
“…This was particularly evident for some bacterial taxa such as Actinobacteria (sp.1 and sp.2), Geobacillus and Wolbachia, which were hosted by P. horvathi and P. tridentatus ( Figure 5). The results are consistent with recent studies showing strong associations between host phylogenetic divergence and phylogenetic divergence of the associated microbiome in several taxa, including humans [72,73], mice [74], birds [75], lizards [76] and insects [77].…”
Section: Codiversification Between Water Striders and Their Microbiomesupporting
confidence: 92%
“…Similarly, germ-free mice exhibit a range of changes in growth rate and fecundityrelated phenotypes (Dubos and Schaedler, 1960). In addition, the host-species specific microbiota appears to be a key regulator of growth phenotypes, as house mice (Mus musculus domesticus) inoculated with the gut microbiota of closely related host species display altered growth curves than when inoculated with their own gut microbiota (Moeller et al, 2019). These results suggest that disruption of the gut microbiota by thermal stress could ultimately affect host growth and reproductive traits, but this hypothesis has not been tested with experiment.…”
Section: Host Life History Traitsmentioning
confidence: 99%
“…In addition, gut-microbiota transplant experiments into axenic hosts have revealed that variation in the microbiota can generate variation in host phenotypes (Faith et al, 2014;Gould et al, 2018). Recently, this gut-microbiota driven variation in host phenotype has been implicated in the adaptive evolution of host populations (Rudman et al, 2019) and species (Moeller et al, 2019), further suggested that the presence of specific microorganisms in the gut is important for host fitness. As temperature regimes change globally, any effect that these changes have on the composition of animal gut microbial communities may alter their functions and lead to consequences for host phenotypes and fitness.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the composition of the gut microbiota can have profound effects on the host’s physiology and morphology, as well as behaviour [ 3 8 ]. Moreover, between-species divergence in the gut microbiota composition could play a role in the establishment of reproductive isolation between species and thus in generating species diversity [ 6 , 9 , 10 ]. Despite recent intensive research on variation in the gut microbiota composition within and between vertebrate species [ 1 , 11 14 ] the factors that generate the gut microbial diversity are still not sufficiently understood, especially in non-mammalian taxa.…”
Section: Introductionmentioning
confidence: 99%